Problematika Pembelajaran Tahfizh Al-Qur’an pada Siswa SDI Tahfizhul Qur’an At-Tauhid Pangkal Pinang - Viyola Romadona; Budianto Budianto (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze the problems encountered in Tahfizhul Quran learning among students at SDI Tahfizh Quran At-Tauhid and to identify the inhibiting factors as well as teachers’ strategies in overcoming memorization difficulties. This research employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation involving tahfizh teachers, students, and the school principal as research subjects. The findings revealed that Tahfizhul Quran learning had been implemented systematically through talaqqi, muroja’ah, and regular memorization evaluations. However, the learning process still faced several major challenges, including students’ difficulties in memorizing long verses and verses with similar lafaz, limited muroja’ah time due to the full day school system, low memorization motivation, and the influence of social environments and gadget use. The inhibiting factors originated from internal aspects such as memory capacity, concentration, and learning motivation, as well as external aspects including family environment, peer influence, and dense school activities. Teachers addressed these obstacles by providing motivation, intensive guidance, enjoyable memorization methods, strengthening muroja’ah activities, and establishing collaboration with parents. This study is expected to contribute as an evaluative reference for improving the effectiveness of Tahfizhul Quran learning in Islamic full day school institutions.